قصور التعبير عن المشاعر "الالكسيثيميا" وعلاقته بمهارات التأقلم لدى طلبة المرحلة الإعدادية - البياتي، وفاء كنعان خضر; حمادي، ميسون عباس (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2021)
هدفت هذه الدراسة إلى معرفة مستوى التعبير والعلاقة بين قصور التعبير عن المشاعر (الاليكسيثيميا) بمهارات التأقلم لدى طلبة المرحلة الإعدادية. وقد تفرع من هذا الهدف مجموعة من الأهداف: 1. التعرف على مستوى قصور التعبير عن المشاعر (الاليكسيثيميا) لدى طلبة المرحلة الإعدادية. 2. التعرف على الفروق في قصور التعبير عن المشاعر (الاليكسيثيميا) لدى طلبة المرحلة الإعدادية حسب متغيري الجنس (ذكور-إناث) والتخصص (علمي _ أدبي) 3. التعرف على مستوى مهارات التأقلم لدى طلبة المرحلة الإعدادية. 4. التعرف على الفروق في مستوى مهارات التأقلم لدى طلبة المرحلة الإعدادية حسب متغيري الجنس (ذكور-إناث) والتخصص (علمي _ أدبي). 5. التعرف على العلاقة الارتباطية بين قصور التعبير عن المشاعر ومهارات التأقلم لدى طلبة المرحلة الإعدادية. بلغت عينة البحث من (600) طالب وطالبة من طلبة المرحلة الإعدادية والثانوية النهارية لمدينة بغداد الكرخ/2 قسم تربية الدورة والسيدية، وبالنسبة لأدوات البحث فقد تم بناء أداة لقياس قصور التعبير عن المشاعر (الاليكسيثيميا)، وبناء أداة لقياس مهارات التأقلم، ومن ثم التحقق من صدقها وثباتها. وقد اعتمد الباحثتان الوسائل الإحصائية التي تلائم البحث وطبيعة أهدافه بناء على استشارة بعض المختصين في مجال الإحصاء وباستخدام الحقيبة الإحصائية للعلوم الاجتماعية (spss). وقد توصلت الباحثتان إلى مجموعة من النتائج ومنها أن طلبة عينة البحث بمستوى عال من قصور التعبير عن المشاعر، وأن طالبات عينة البحث أكثر من الطلاب في متغير قصور التعبير عن المشاعر، فضلا على أن الطلاب كانوا أكثر من الطالبات في متغير مهارات التأقلم. وبناء على نتائج البحث قدمت الباحثتان بعض التوصيات والمقترحات.
This study aimed to find out the level of expression and the relationship between the failure to express feelings (alexithymia) and the coping skills of students in the middle school. This goal has branched out from a group of goals: 1- Identifying the level of deficiency in expressing feelings (alexithymia) among middle school students. 2- Identifying the differences in the lack of expression of feelings (alexithymia) among middle school students according to the variables of sex (males- females) and specialization (scientific- literary). 3- Identifying the level of coping skills of middle school students. 4- Identifying the differences in the level of coping skills of middle school students according to the variables of sex (male- female) and specialization (scientific- literary). 5- Identify the correlation between the lack of expression of feelings and the coping skills of middle school students. The research sample amounted to (600) male and female students from the middle and high school day of the city of Baghdad Al-Karkh/ 2 Department of Course and Master Education. As for the research tools, a tool was built to measure the failure of expression of feelings (alexithymia), and a tool was built to measure coping skills, and then verify From its sincerity and constancy. The two researchers have adopted statistical methods that suit the research and the nature of its objectives based on the advice of some specialists in the field of statistics and by using the Statistical Portfolio for Social Sciences (SPSS). The two researchers reached a set of results, including that the students of the research sample had a high level of deficiency in the expression of feelings, and the students of the research sample had more than the students in the variable of deficient expression of feelings, in addition to that the students were more than the students in the variable coping skills.
Keywords: علم نفس الاجتماعي -- الاضطرابات النفسية -- طلبة المرحلة الإعدادية -- العراق